Akibat Hukum Penetapan Tanah Terlantar Terhadap Keberlakuan Hak Tanggungan Sebagai Jaminan Kebendaan Bagi Kreditur - Silva Fransisca Utami; Rosalinda Elsina Latumahina (Media Hukum Indonesia (MHI), 2026)
Indonesia’s participation in international peace institutions has long been a cornerstone of its foreign policy, rooted in the constitutional mandate of Article 1 Paragraph 4 of the 1945 Constitution, which calls for active contribution to world peace based on independence and social justice. The emergence of the Board of Peace as an international institution focused on conflict resolution and peacebuilding raises significant questions regarding the legal basis, scope, and implications of Indonesia’s membership under national law. This study aims to analyze the legality of Indonesia’s membership in the Board of Peace, examine the applicable national legal framework governing international institutional participation, and formulate a normative understanding of how such membership aligns or conflicts with existing Indonesian law. This study employs a normative legal research method utilizing a statutory and conceptual approach. The results indicate that while Indonesia’s constitution and international treaty law provide a general basis for participation in international organizations, specific legislative frameworks governing membership conditions, obligations, and accountability mechanisms remain underdeveloped.